EVALUASI USABILITY WEBSITE BEHANDLE OPERATION SYSTEM CUSTOMER PT. MULTI TERMINAL INDONESIA MENGGUNAKAN METODE SYSTEM USABILITY SCALE - Ririmasse, Rajiv Prayoga; Badrul, Mohammad (JURNAL ILMIAH INFORMATIKA, 2024)
Websites are one of the most widely used internet facilities, presenting information interactively to users. However, website evaluation should not be ignored to ensure an optimal user experience. Although the Behandle Operation System Customer PT. Multi Terminal Indonesia has been launched since 2021, data shows that the number of customers registering on this platform has decreased from year to year. The number of customers who registered in 2021 reached 1,337 customers, in 2022 the number of registrants decreased to 906, and in 2023 it decreased again to 847. This decline is a serious concern for the company, because it can interfere with the effectiveness and efficiency of their operations. To overcome this problem, a comprehensive evaluation of website usability needs to be carried out. The System Usability Scale (SUS) method was chosen because of its ease of use and reliability in evaluating website usability. The results of the study showed an average SUS score of 65, indicating an acceptable level of usability. However, the findings from this evaluation lead to recommendations for improving the user interface, minimizing errors, and improving service quality. These recommendations are expected to improve user experience and improve SUS values to achieve higher standards.